Performance assessment of a new intra–mobility solution for healthcare wireless sensor networks. (20th March 2014) - Caldeira, J.M.L.P.; Rodrigues, J.J.P.C.; Gilg, M.; Lorenz, P.
The use of wireless sensor networks (WSNs) in healthcare is a key issue. These technologies can improve the way patients are monitored in an infirmary or a hospital. The healthcare WSNs (HWSNs) assume the use of WSNs for health support, collecting and send patients' health parameters wirelessly to remote monitoring systems. These applications bring many new challenges to traditional WSNs. These challenges include the continuous support connectivity to mobile nodes. The ability to let patients moving around when hospitalised is important to promote their quality of life. Managing the transitions of access points' attachment when a node moves across several coverage areas is on top of research topics in HWSNs. This paper studies the performance of a new handover mechanism to support intra–mobility of nodes for HWSN, called Hand4MAC. The evaluation is performed through a laboratory testbed and it was compared to the most used handover solutions. The results shown that Hand4MAC is more efficient in number of exchanged messages and it could ensure almost continuous connection to the nodes.